Why are Switzerland's foreign assets so low? The growing financial exposure of a small open economy - Nicolas Stoffels; Cédric Tille (Federal Reserve Bank of New York, 2007)
Switzerland's international investment position shows a puzzling feature since 1999: Large and persistent current account surpluses have failed to boost the value of Swiss foreign assets. In this paper, we link this pattern to the substantial increase in the leveraging of Switzerland's international assets and liabilities over the last twenty years, which we document in detail. We estimate the impact of exchange rate and asset prices movements on Swiss net foreign assets, and show that they led to substantial valuations losses since 1999, accounting for between one-quarter and one-half of the gap between the net foreign assets and cumulated current account flows. We show how these adverse valuation effects have erased Switzerland's advantage in terms of the yield on its net foreign asset position.
Keywords: F32; F33; F36; 330; international leverage; valuation effect; external position; Auslandsvermögen; Direktinvestition; Portfolio-Investition; Zahlungsbilanz; Kleines-offenes-Land; Schweiz